Resilience ability and small medium enterprise (SME) survival rate in the middle of business environmental fluctuation - Ahmad Syaiful Affa; Muh. Ghafur Wibowo; Izra Berakon (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2020)
Purpose – This study examines the effect of organizational resilience variables on the firm’s survival rate and the moderating role of environmental turbulence variables in the relations of organizational resilience and firm survival.Method – This study uses simple regression to test research hypotheses. Primary data in the form of questionnaires are obtained from Small and Medium Enterprises (SMEs) in Java.Result – The analysis shows that organizational resilience variables can improve the firm’s survival. However, this study did not find the moderating role of environmental turbulence in influencing the relationship between organizational resilience variables and firm survival.Implication – This study can help scholars and practitioners to understand more of the mechanism of organizational resilience and its impact on survival on smaller firms.Originality – This study offer the empirical study of firm survival on small-medium enterprise setting in Indonesia.